Compliance Costs of Regulation for Small Business - Lewis , Phil; Richardson , Alice; Corliss , Michael (Journal of Law and Governance, 2014)
There has been growing concern about the extent of government regulation in Australia and its impact on small business. This paper examines the results of a survey of small businesses in NSW and Victoria regarding their experiences relating to compliance with government regulation, the costs to business, and factors inhibiting performance. The paper describes the development of the survey instrument, the administration of the survey, a description of the sample, results of the quantitative part of the survey, and an overview of business owners’ comments provided by respondents.